2014
DOI: 10.1111/jth.12499
|View full text |Cite
|
Sign up to set email alerts
|

Family history of venous thromboembolism (VTE) and risk of recurrent hospitalization for VTE: a nationwide family study in Sweden

Abstract: To cite this article: Z€ oller B, Ohlsson H, Sundquist J, Sundquist K. Family history of venous thromboembolism (VTE) and risk of recurrent hospitalization for VTE: a nationwide family study in Sweden. J Thromb Haemost 2014; 12: 306-12.Summary. Background: Data concerning the importance of a family history of venous thromboembolism (VTE) for the risk of recurrent VTE are sparse. The aim of this nationwide study was to determine whether a family history of VTE is a risk factor for recurrent hospitalization for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The HR of recurrent VTE hospitalisation in individuals with two affected parents was 1.92 (95 % CI 1.44-2.58). These three studies (72)(73)(74) are in line with studies that have shown Factor V Leiden to be a modest or no risk factor for recurrence in a large number of studies (75). In a study by Lijfering et al even individuals with homozygous FV Leiden and/or homozygous FII G20210A or double heterozygous carriers of FV Leiden and FII G20210A did not have a high risk of recurrent VTE (76).…”
Section: Family History and Recurrent Vtesupporting
confidence: 73%
See 1 more Smart Citation
“…The HR of recurrent VTE hospitalisation in individuals with two affected parents was 1.92 (95 % CI 1.44-2.58). These three studies (72)(73)(74) are in line with studies that have shown Factor V Leiden to be a modest or no risk factor for recurrence in a large number of studies (75). In a study by Lijfering et al even individuals with homozygous FV Leiden and/or homozygous FII G20210A or double heterozygous carriers of FV Leiden and FII G20210A did not have a high risk of recurrent VTE (76).…”
Section: Family History and Recurrent Vtesupporting
confidence: 73%
“…However, two family studies have found no association with FH of VTE and risk for recurrent disease (72,73). A Swedish nationwide study found a significant association (74). The HR was 1.20 (95 % CI 1.10-1.32) for subjects with parent history and 1.30 (95 % CI 1.14-1.49) for VTE patients with sibling history, which is much lower than the familial risk for primary VTE (▶ Table 1 and ▶ Table 2).…”
Section: Family History and Recurrent Vtementioning
confidence: 99%
“…Family history of VTE has been found to be a risk factor for first VTE, even in the absence of the known thrombophilias (51,52). Heritability has also been found to be a predictor of hospitalization for recurrent VTE in a Swedish study (53). The effect of heritability was strongest in younger patients, suggesting a genetic contribution.…”
Section: Recurrent Vtementioning
confidence: 94%
“…84,85 A Swedish nationwide family study showed a weak but significant association. 86 The HR was 1.2 for VTE patients with parent history and 1.3 for VTE cases with sibling history, which is much lower than the FRR for first event of VTE (►Table 2). 86 The HR of recurrent VTE in patients with two affected parents was 1.9 (i.e., a biological gradient compared with one affected parent).…”
Section: Family History Of Venous Thromboembolism and Spontaneous Venmentioning
confidence: 79%
“…86 The HR was 1.2 for VTE patients with parent history and 1.3 for VTE cases with sibling history, which is much lower than the FRR for first event of VTE (►Table 2). 86 The HR of recurrent VTE in patients with two affected parents was 1.9 (i.e., a biological gradient compared with one affected parent). Two recent studies have confirmed that FH of VTE is an independent risk factor for recurrent VTE even in the presence of established genetic determinants for VTE.…”
Section: Family History Of Venous Thromboembolism and Spontaneous Venmentioning
confidence: 79%